Khitan Perempuan dalam Tinjauan Tradisi dan Hukum Islam - Aris Abdul Ghoni; Gadis Herningtyasari; Tri Handayani; Imam Khoirul Ulumuddin (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2023)
The rules of Islamic fiqh and sharia are built on the aim of realizing human benefit in this world and the hereafter, there is not a single law of Allah that does not carry out the mission of universal human benefit. This research examines the practice of Female Circumcision in light of Islamic tradition and law. This research aims to describe female circumcision, analyzing female circumcision according to Islamic tradition and law. This research is a type of field research with an anthropological approach. Data collection methods use interview techniques, observation and documentation studies as well as qualitative descriptive data analysis methods. This research shows that the majority of people in the Pantura region including Kendal, Semarang, Demak and Kudus regarding female circumcision interpret female circumcision textually and contextually. Female circumcision is a tradition and symbol to make one's daughter a good person. Female circumcision aims to get rid of suker which according to Javanese philosophy is interpreted as a bad character and parents hope that one day their child will become a virtuous human being.AbstrakKaidah fiqh dan syari’at Islam dibangun atas dasar tujuan untuk mewujudkan kemaslahatan manusia di dunia dan akhirat, tidak satu pun hukum Allah yang tidak mengemban misi kemaslahatan manusia secara universal. Penelitian ini mengkaji tentang praktik Khitan Perempuan dalam tinjauan tradisi dan hukum Islam. Penelitian ini bertujuan untuk mendeskripsikan khitan bagi perempuan, menganalisis khitan perempuan menurut tinjauan tradisi dan hukum Islam. Penelitian ini merupakan jenis penelitian lapangan (field research) dengan pendekatan antropologis. Metode pengumpulan data menggunakan teknik wawancara, observasi dan studi dokumentasi serta metode analisis data deskriptif kualitatif. Penelitian ini menunjukkan bahwa mayoritas masyarakat kawasan pantura meliputi Kendal, Semarang, Demak dan Kudus terhadap khitan perempuan memaknai khitan perempuan secara tekstual dan kontekstual. Khitan perempuan merupakan salah satu tradisi dan simbol untuk menjadikan anak perempuannya sebagai pribadi yang baik. Khitan perempuan bertujuan untuk membuang suker yang menurut filosofi Jawa dimaknai sifat buruk dan orang tua berharap kelak anaknya menjadi manusia yang berbudi luhur.